Răspuns :
1
√25 +√36 -√49=5+6-7=4
√100 * √ 16 - √144=10×4-12=40-12=28
3 *√225 + 12√121 - √169=3×15+12×11-13=45+132-13=164
5√81 - √64 * √196 + 2√100=5×9-8×14+2×10=45-112+20=-47
2
√2305 * (√225 - √1225) + √1600= √2305 * (15 - 35) + 40=
=√2305 * (-20) + 40=-20√2305+40=20(20-√2305)
√5 *√25 + √5 *√49 - √9 *√16=5√5 + 7√5 - 3*4=12√5-12=12(√5-1)
√25 +√36 -√49=5+6-7=4
√100 * √ 16 - √144=10×4-12=40-12=28
3 *√225 + 12√121 - √169=3×15+12×11-13=45+132-13=164
5√81 - √64 * √196 + 2√100=5×9-8×14+2×10=45-112+20=-47
2
√2305 * (√225 - √1225) + √1600= √2305 * (15 - 35) + 40=
=√2305 * (-20) + 40=-20√2305+40=20(20-√2305)
√5 *√25 + √5 *√49 - √9 *√16=5√5 + 7√5 - 3*4=12√5-12=12(√5-1)
√25+√36 -√49=5+6-7=11-7=4
√100* √16- √144=10*4-12=40-12=28
3*√225+12*√121-√169=3*15+12*11-13=164
5√81 - √64 * √196 + 2√100=5*9-8*14+2*10=45-112+20= - 47
√2304 * ( √225 - √1225) + √1600=48*(15 - 35)+40=48*(-20)+40= - 960+40=
= -920
√5 *√ 25 + √ 5 * √ 49 -√ 9 * √16= √5*(5+7)-3*4=12√5-12=12*(√5-1)
√100* √16- √144=10*4-12=40-12=28
3*√225+12*√121-√169=3*15+12*11-13=164
5√81 - √64 * √196 + 2√100=5*9-8*14+2*10=45-112+20= - 47
√2304 * ( √225 - √1225) + √1600=48*(15 - 35)+40=48*(-20)+40= - 960+40=
= -920
√5 *√ 25 + √ 5 * √ 49 -√ 9 * √16= √5*(5+7)-3*4=12√5-12=12*(√5-1)